Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1046/j.1464-410x.1997.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial laser coagulation in the treatment of benign prostatic hyperplasia using a diode‐laser system with temperature feedback

Abstract: Objective To report the initial results of the treatment than heating of the median lobe or base of the prostate.Patients improved markedly 1 and 3 months after of patients with benign prostatic hyperplasia using interstitial laser coagulation (ILC) performed with a treatment; the respective mean symptom scores improved from 20.6 before treatment to 9.4 and 6.9, temperature-sensing laser system. Patients and methods Twenty-five patients were treated the maximum urinary flow rates from 9.1 mL/s to 14.1 mL/s and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 1 publication
(1 reference statement)
1
20
2
Order By: Relevance
“…The results in both groups are comparable with those reported by others [7,20,23,24]. Comparing TUMT and the control group, the standard operation was the most effective, as others report [13,17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results in both groups are comparable with those reported by others [7,20,23,24]. Comparing TUMT and the control group, the standard operation was the most effective, as others report [13,17].…”
Section: Discussionsupporting
confidence: 88%
“…ILC has documented efficacy and an acceptable frequency of side-effects [4][5][6][7]. In some aspects ILC seems to offer an advantage over TURP; blood loss is minimal and the risk of TUR syndrome is eliminated, as saline rather than glycine is used as the irrigant.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The incidence of sexual dysfunction is negligible after TUNA; several studies reported no ED or retrograde ejaculation. 20 -22 Only one study, a prospective multicentre trial in the US, found less than 1 and 2% of retrograde ejaculation and ED, respectively.…”
Section: Minimally Invasive Therapiesmentioning
confidence: 99%
“…As the optimal temperature for coagulation is estimated to be about 85 C the aim of the treatment was to reach and maintain this temperature at the site of treatment during the entire treatment cycle. A temperature-triggered feedback system was built into the laser unit so that during treatment the temperature was monitored continuously, and the temperature and power output formed a feedback loop that sought to maintain a temperature of 85 C. 4 Suprapubic catheters were removed when adequate voiding was demonstrated at scheduled follow-up visits (1, 2 or 4 weeks).…”
Section: Laser Proceduresmentioning
confidence: 99%
“…We have also recently reported on the initial results using a diode laser system with temperature feedback. 4 Therefore we also report on long-term follow-up results using such a system.…”
Section: Introductionmentioning
confidence: 99%